Terrestrial gamma radiation dose study to determine the baseline for environmental radiological health practices in Melaka state, Malaysia - Ramli, Ahmad Termizi; Sahrone, S; Wagiran, Husin (2005)
Environmental terrestrial gamma radiation dose rates were measured throughout Melaka, Malaysia, over a period of two years, with the objective of establishing baseline data on the background radiation level. Results obtained are shown in tabular, graphic and cartographic form. The values of terrestrial gamma radiation dose rate vary significantly over different soil types and for different underlying geological characteristics present in the study area. The values ranged from 54 ± 5 to 378 ± 38 nGy h-1. The highest terrestrial gamma dose rates were measured over soil types of granitic origin and in areas with underlying geological characteristics of an acid intrusive (undifferentiated) type. An isodose map of terrestrial gamma dose rate in Melaka was drawn by using the GIS application 'Arc View'. This was based on data collected using a NaI(Tl) scintillation detector survey meter. The measurements were taken at 542 locations. Three small 'hot spots' were found where the dose rates were more than 350 nGy h-1. The mean dose rates in the main population areas in the mukims (parishes) of Bukit Katil, Sungai Udang, Batu Berendam, Bukit Baru and Bandar Melaka were 154 ± 15, 161 ± 16, 160 ± 16, 175 ± 18 and 176 ± 18 nGy h -1, respectively. The population-weighted mean dose rate throughout Melaka state is 172 ± 17 nGy h-1. This is lower than the geographical mean dose rate of 183 ± 54 nGy h-1. The lower value arises from the fact that most of the population lives in the central area of the state where the lithology is dominated by sedimentary rocks consisting of shale, mudstone, phyllite, slate, hornfels, sandstone and schist of Devonian origin which have lower associated dose rates. The mean annual effective dose to the population from outdoor terrestrial gamma radiation was estimated to be 0.21 mSv. This value is higher than the world average of 0.07 mSv.